Heavy rainfall equations for the “Manuel Alves da Natividade” river watershed, Tocantins, Brazil - Silva Neto, Virgílio Lourenço; Viola, Marcelo Ribeiro (Científica, 2017)
Knowledge of the equation that relates intensity, duration and frequency of heavy rainfall is of great technical interest in hydraulic projects. The aim of this study was to obtain the intensity-duration-frequency (IDF) relationship of heavy rainfall in the Manuel Alves da Natividade river watershed, located in the southeastern region of the state of Tocantins, Brazil. We used the rainfall disaggregation model, with adjustment of the heavy rainfall equation by nonlinear multiple regression, in addition to historical series of six pluviometric stations, obtained from the Hydrological Information System of the National Water Agency (Hidroweb-ANA). Gumbel probability distribution was adequate to model the frequency distribution of annual maximum daily rainfall series, according to the Kolmogorov-Smirnov test at 20% significance level. The heavy rainfall equations presented good statistical quality, with coefficients of determination above 0.92, which characterize them as useful tools in the context of water resource management in the Manuel Alves da Natividade river watershed.